ADAMDEC1 accelerates GBM progression via activation of the MMP2-related pathway - Qi, Huimin; Wang, Ping; Sun, Hongliang; Li, Xiaohan; Hao, Xinwei; Tian, Wenxiu; Yu, Liting; Tang, Jiajian; Dong, Junhong; Wang, Hongmei (Frontiers in Oncology, 2022)
ADAM (A Disintegrin and Metalloprotease) gene related family including ADAM, ADAMTS and ADAM-like decysin-1 have been reported to play an important role in the pathogenesis of multiple diseases, including cancers (lung cancer, gliomas, colorectal cancer, gastrointestinal cancer). However, its biological role in gliomas remains largely unknown. Here, we aimed to investigate the biological functions and potential mechanism of ADAMDEC1 in gliomas. The mRNA and protein expression levels of ADAMDEC1 were upregulated in glioma tissues and cell lines. And ADAMDEC1 showed a phenomenon of "abundance and disappear" expression in gliomas and normal tissues that the higher the expression of ADAMDEC1 presented the higher the malignancy of gliomas and the worse the prognosis. High expression of ADAMDEC1 was associated with immune response. Knockdown of ADAMDEC1 could decrease proliferation and colony forming ability of LN229 cells, whereas ADAMDEC11 overexpression has opposite effects in LN229 cells in vitro. Furthermore, we identified ADAMDEC1 accelerates GBM progression via activation of MMP2 pathway. In the present study, we found that the expression levels of ADAMDEC1 were significantly elevated compared with other ADAMs by analyzing the expression levels of ADAM family proteins in gliomas. This suggests that ADAMDEC1 has potential as a glioma clinical marker and immunotherapy target.